The Logic of the CAP : Politics or Economics? - Henning, Christian H.C.A.; Struve, Carsten; Brockmeier, Martina (World Bank, Washington, DC, 2017)
This paper derives an applied general political economy model incorporating a model of political decision making into a computable general economic equilibrium model. Political decision making among a set of legislators is modeled via a mean voter decision rule derived from a modified non cooperative legislative bargaining game of a Baron Ferejohn type. The model allows a simultaneous analysis of political and economic factors determining policy outcome and is applied to simulate future Common Agricultural Policy (CAP) under various political and economic scenarios.